(untitled) (Communications in Mathematical Research, 2021)
In this paper we mainly consider little Hankel operators with square-integrable symbols on the weighted Bergman spaces of the unit ball. We obtain that Schatten class of little Hankel operators is equivalent to Schatten class of positive Toeplitz operators under the conditions that SMO(f) ∈ L^p2 (B_n, dλ) and 2 ≤ p < ∞, which is very important to research the relation between Toeplitz operators and little Hankel operators.